NEUROPSYCHOLOGY OF SCHIZOPHRENIA - Hugo Selma Sánchez (CAEN, 2008)
Neuropsychology has had an explosive grow in the last decades. It contributions to the fields of Psychiatry are growing in an exponential rate. Research related to schizophrenia has bringing new views of the nature of the disease, at the same time offering contradictions and questions pending to resolve. The present article exposes the most relevant discoveries in the neuropshychology of schizophrenia neuroanatomy dysfunctions, development neurofuntionality, alterations in neurotransmitters and cognitive deficiencies) and areas for exploring.